iPads in the classroom: trials in a technical college in Qatar - Cheri Macleod (22401022) (2015)
This paper describes a small research project undertaken in a technical college in Qatar on the use of iPads in the classroom. iPads were trialed for a semester each in mathematics and physics classes; students completed pre- and post-surveys. Classroom observations were carried out and interviews were conducted with both faculty (N=3) and students (N=19). Over 80% of students reported positively on the iPad as being “helpful” to “very helpful” for learning new things and course materials, for increasing their interaction with online course materials and getting course information and for exploring additional material related to course topics. Faculty perceptions of iPad use in class were also positive. Other Information Published in: Learning and Teaching in Higher Education: Gulf Perspectives License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.18538/lthe.v12.n1.170 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.